Closing the Dictatorship and Opening Free Trade Agreements. Transnational Networks of the New Right-Wing: Idu, Upla and the Chilean Renovación Nacional Party, 1983-1997. [Cerrando la Dictadura y Abriendo Los Tratados de Libre Comercio.Redes Transnacionales Partidarias de la Nueva Derecha: Idu, Upla y el Partido Renovación Nacional de Chile, 1983-1997] - Pérez-Contreras, A (Universidad de Concepcion, 2022)
This article analyzes both tensions and implications of transnational relations in the new Chilean right-wing. In particular, it focuses its attention on the formation of the International Democrat Union (IDU), together with the articulation of the Union of Latin American Parties (UPLA) with National Renovation. The hypothesis that we propose affirms that such articulation was a vector in the promotion of the free market, reaffirming the cleavage that had occurred within the party during the transition between “hard” and “liberals”. Through the debate of the first Free trade agreements signed since the democratic return, as well as unpublished sources of militant files, we evidence the configuration of groups, conflicts and representation of interests in National Renovation is evidenced. This indicates a party more prone to conflicting tendencies than properly liberal as has sustained by the bibliography. © 2022, Universidad de Concepcion. All rights reserved.